2012
DOI: 10.3109/19401736.2012.683184
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the giant pill millipede, Sphaerotheriidae sp. (Myriapoda: Diplopoda: Sphaerotheriida)

Abstract: The complete mitochondrial genome (mitogenome) of the millipede Sphaerotheriidae sp. has been studied. The genome is 14,970 bp long and contains the typical complement of 13 protein-coding genes, 22 transfer RNA genes, and 2 ribosomal RNA genes. Gene order in Sphaerotheriidae sp. mitogenome is assumed to represent the myriapod ground pattern, which is shared by myriapod-chelicerate clade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…(Genbank: EF576853) were selected as out-groups. The phylograms obtained from BI and ML (data not shown) were all strongly indicated that Sphaerotheriida with an ancestral gene order of mitogenome for the Helminthomorpha was located in the basal branch (Gai et al 2008;Dong et al 2012). The topological structures between Spirobolida, Callipodida, Spirostreptida, Playtdesmida, and Julida were similar with that observed for other previously studies (Woo et al 2007;Brewer et al 2013).…”
supporting
confidence: 85%
“…(Genbank: EF576853) were selected as out-groups. The phylograms obtained from BI and ML (data not shown) were all strongly indicated that Sphaerotheriida with an ancestral gene order of mitogenome for the Helminthomorpha was located in the basal branch (Gai et al 2008;Dong et al 2012). The topological structures between Spirobolida, Callipodida, Spirostreptida, Playtdesmida, and Julida were similar with that observed for other previously studies (Woo et al 2007;Brewer et al 2013).…”
supporting
confidence: 85%
“…Gene order in Prionobelum sp. which is the basal lineage of the millipede mt genome is assumed to represent the millipede or myriapod ground pattern (Dong et al 2012b), and inversion of the entire side of the genome occurred as a common event in the order Polydesmida lineage proposed in this study. In our gene order comparison of these millipedes, phylogenetic results are mainly concordant with gene arrangement analyses (Figure 5).…”
Section: Discussionmentioning
confidence: 92%
“…and Limulus polyphemus (Dong et al 2012b). The overall arrangement of the genes around the Asiomorpha coarctata and Xystodesmus sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations